25-Hydroxyvitamin D, IL-31, and IL-33 in Children with Allergic Disease of the Airways. (25th June 2014) - Bonanno, Anna; Gangemi, Sebastiano; La Grutta, Stefania; Malizia, Velia; Riccobono, Loredana; Colombo, Paolo; Cibella, Fabio; Profita, Mirella
Abstract : Low vitamin D is involved in allergic asthma and rhinitis. IL-31 and IL-33 correlate with Th2-associated cytokines in allergic disease. We investigated whether low vitamin D is linked with circulating IL-31 and IL-33 in children with allergic disease of the airways. 25-Hydroxyvitamin D [25(OH) Vit D], IL-31, and IL-33 plasma levels were measured in 28 controls (HC), 11 allergic rhinitis (AR) patients, and 35 allergic asthma with rhinitis (AAR) patients. We found significant lower levels of 25(OH) Vit D in AR and in AAR than in HC. IL-31 and IL-33 plasma levels significantly increased in AAR than HC. IL-31 and IL-33 positively correlated in AR and AAR. 25(OH) Vit D deficient AAR had higher levels of blood eosinophils, exacerbations, disease duration, and total IgE than patients with insufficient or sufficient 25(OH) Vit D. In AAR 25(OH) Vit D levels inversely correlated with total allergen sIgE score and total atopy index. IL-31 and IL-33 did not correlate with 25(OH) Vit D in AR and AAR. In conclusion, low levels of 25(OH) Vit D might represent a risk factor for the development of concomitant asthma and rhinitis in children with allergic disease of the airways independently of IL-31/IL-33 Th2 activity.